The Concept of a Philosophical Jurisprudence : Essays and Reviews 1926-51. - Oakeshott, Michael (Michael Oakeshott Selected Writings, 3., 2011)
This volume brings together for the first time over a hundred of Oakeshott's essays and reviews, written between 1926 and 1951, that until now have remained scattered through a variety of scholarly journals, periodicals and newspapers. A new editorial introduction explains how these pieces, including the lengthy essay on the philosophical nature of jurisprudence that occupies an important position in Oakeshott's work, illuminate his other published writings. The collection throws new light o ...